2005
DOI: 10.1002/elan.200403155
|View full text |Cite
|
Sign up to set email alerts
|

Solid State Electrochemical Oxidation Mechanisms Of Morin in Aqueous Media

Abstract: The mechanism of electrochemical oxidation of morin has been studied using cyclic, differential pulse and squarewave voltammetry techniques in aqueous electrolyte with solid, insoluble morin hydrate mechanically transferred to a glassy carbon electrode surface, over a wide pH range. The oxidation mechanism proceeds in sequential steps, related with the hydroxyl groups in the three aromatic rings and the oxidation is pH dependent over part of the pH range the oxidation potentials are shifted to lower values wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
47
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 82 publications
(53 citation statements)
references
References 32 publications
(26 reference statements)
6
47
0
Order By: Relevance
“…The electrochemistry of this selected series of synthesized coumarinnaphthalene-stilbene hybrids (6)(7)(8)(9)(10) showed that the difference in the position of the hydroxyl substituents have only a slightly effect upon the electroactivity of the selected coumarins.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…The electrochemistry of this selected series of synthesized coumarinnaphthalene-stilbene hybrids (6)(7)(8)(9)(10) showed that the difference in the position of the hydroxyl substituents have only a slightly effect upon the electroactivity of the selected coumarins.…”
Section: Discussionmentioning
confidence: 97%
“…The phenol group is irreversibly oxidised in compounds 6, 7, 8, and 10, and the catechol group is reversibly oxidised in compound 9. The oxidation products of the coumarin-naphthalene-stilbene hybrids (6)(7)(8)(9)(10) The monohydroxylated compounds 6-8, irreversible pH-dependent oxidation process, occurs with one electron and one proton transfer, following the phenol oxidation mechanism [43]. Compound 6, with the para position to the hydroxyl group occupied, formed a single oxidation product corresponding to a catechol moiety, Scheme 3.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations